Transforming Police-Community Relations: The Role of Experiential Learning in Law Enforcement Training - Kyle Znamenak (Adult Education Research Conference, 2025)
An ongoing case study that explores the integration and effectiveness of experiential learning methodologies in a police officer community-relations training program and its influence on transformative learning.
Keywords: experiential learning; police training; transformative learning